Universidad: índole, entronque de los saberes e interdisciplinariedad - Sellés, Juan Fernando (Mercurio Peruano, 2013)
We study the nature of university. We distinguish between the analytical and systemic method. We show that the theory of knowledge permits to sheds light on the distinction between the sciences; and that ethics and anthropology allow us to join them. We conceive the university as a free system without equilibrium because is the motor of the change according the truth.
Keywords: university, analysis, synthesis, sciences, theory of knowledge, ethics, anthropology, change, truth.